Minnesota - Hasday, Judy L (New York Children's Press, 2003)
Takes the reader on a tour of the state called "The North Star State," emphasizing its geography, history, government, and culture
Includes bibliographical references (p. 76) and index
Hurg
5 8
Keywords: Minnesota -- Juvenile literature; Minnesota